Climate Risk and Bank Performance: What Role does Corporate Social Responsibility Play? - Khemiri , Mohamed Ali; Saidi, Hichem; Hakimi, Abdelaziz (International Journal of Energy Economics and Policy, 2025)
Over the past decade, climate risk has emerged as one of the most urgent global challenges, posing serious threats to ecosystems, economic stability, and human well-being. A substantial body of research has explored the macroeconomic implications of climate risk. However, studies examining its micro-level effects, particularly on financial institutions remain relatively scarce. This imbalance underscores the need for deeper investigation into how climate risk influences bank-level performance. This paper explores whether corporate social responsibility (CSR) can mitigate the negative effect of climate risk on bank performance. The paper uses a sample of MENA banks from 2010 to 2022 and the system generalized method of moments (SGMM) model was used as an empirical approach. The findings of this paper support three major conclusions. First, climate risk was negatively and significantly associated with the bank performance measured by return on assets (ROA) and return on equity (ROE). Second, CSR scores were positively and significantly linked to bank profitability. Third, the findings indicated that banks in the MENA region benefit from an interactional between CSR and climate risk since it increases bank performance. This research completes an important missing piece of the debate on the moderating role of Corporate Social Responsibility (CSR) on the climate risk-bank performance interaction. This research addresses a significant gap in the ongoing debate surrounding the moderating role of CSR in the relationship between climate risk and bank performance. Findings of this study offer several practical insights. Notably, CSR initiatives may serve as an important mechanism in mitigating the adverse impact of climate risk on banking outcomes.